2023
DOI: 10.1007/s12265-023-10389-3
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Systolic Function After 3 Months of SGLT2 Inhibitor Therapy in Heart Failure Patients with Reduced Ejection Fraction

Abstract: Not much is known about the effects of sodium-glucose cotransporter 2 inhibitors (SGLT2i) on echocardiographic parameters of left ventricular (LV) systolic function in patients with heart failure and reduced ejection fraction (HFrEF). We prospectively included 59 outpatients with HFrEF: 41 patients received SGLT2i with OMT (SGLT2i+ group), whereas eighteen patients received OMT without SGLT2i (SGLT2i− group). Myocardial work index (MWI), 3D ejection fraction (3D LVEF), and global longitudinal strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…In a retrospective study with a longer follow-up, an improvement in left ventricular (LV) function was observed, but only in patients affected by T2DM [14]. In diabetic and non-diabetic patients, an improvement in ventricular function was observed, but only during a short-term follow-up [15,16]. Interestingly, this study showed an improvement in LV and right ventricular (RV) function.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…In a retrospective study with a longer follow-up, an improvement in left ventricular (LV) function was observed, but only in patients affected by T2DM [14]. In diabetic and non-diabetic patients, an improvement in ventricular function was observed, but only during a short-term follow-up [15,16]. Interestingly, this study showed an improvement in LV and right ventricular (RV) function.…”
Section: Introductionmentioning
confidence: 63%
“…Indeed, a recent metanalysis demonstrated the relationship between SGLT2i and an improvement in LV, but not in RV function. Mustapic et al [15,16], in a single-blind randomized study, showed the beneficial effects of SGLT2i on LV and RV function in optimally treated HFrEF patients, but over a short-term follow-up. Over a longer follow-up, the retrospective study of Hwang et al [14] showed an improvement in LV function, but only in patients affected by T2DM who were not taking sacubitril/valsartan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 58 Real-world outpatient data suggest that the addition of dapagliflozin to optimal medical therapy of HF with reduced ejection fraction improves advanced echocardiographic parameters including left ventricular global longitudinal strain and myocardial work index. 59 Two-dimensional speckle-tracking echocardiography provides substantial information concerning the early evaluation of the beneficial effects of SGLT2i on myocardial function. 60 …”
Section: Patients With Heart Failurementioning
confidence: 99%